2018
DOI: 10.1038/s41598-018-24426-8
|View full text |Cite
|
Sign up to set email alerts
|

Regions of open water and melting sea ice drive new particle formation in North East Greenland

Abstract: Atmospheric new particle formation (NPF) and growth significantly influences the indirect aerosol-cloud effect within the polar climate system. In this work, the aerosol population is categorised via cluster analysis of aerosol number size distributions (9–915 nm, 65 bins) taken at Villum Research Station, Station Nord (VRS) in North Greenland during a 7 year record (2010–2016). Data are clustered at daily averaged resolution; in total, we classified six categories, five of which clearly describe the ultrafine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 69 publications
5
68
0
Order By: Relevance
“…In addition, only Browse et al () included SOA formation, but their model considered only monoterpenes from terrestrial sources as possible aerosol precursors. Importantly, modeling studies have not captured the increased particle formation with decreasing sea ice extent observed by Dall'Osto et al (, ; Figure ).…”
Section: Regional Arctic Processesmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, only Browse et al () included SOA formation, but their model considered only monoterpenes from terrestrial sources as possible aerosol precursors. Importantly, modeling studies have not captured the increased particle formation with decreasing sea ice extent observed by Dall'Osto et al (, ; Figure ).…”
Section: Regional Arctic Processesmentioning
confidence: 93%
“…Few studies have attempted to quantify the impact of Arctic warming and sea ice loss on natural aerosol. Notably, the occurrence of particle nucleation events at both Zeppelin and Nord has been anti‐correlated with sea ice extent in the last decade (Figure ); decreased sea ice extent is related to increased frequency of particle formation and growth during summer (Dall'Osto et al, , ). This work has further shown that particle formation occurred when air masses had traveled over areas of open water and broken ice, highlighting the importance of both open water and marginal ice zones as sources of aerosol precursors.…”
Section: Regional Arctic Processesmentioning
confidence: 99%
“…S6b, d). Following terminology developed in previous work (Dall'Osto et al, 2017a, 2018b the remaining aerosol clusters can be classified as follows:…”
Section: K-mean Smps Cluster Analysismentioning
confidence: 99%
“…First, Dall'Osto et al (2017a) suggested that the microbiota of sea ice and the sea-ice-influenced ocean were a significant source of atmospheric nucleating particles concentrations (N 1-3 nm ). Second, within two different Arctic locations across large temporal scales (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016) new particle formation was associated with air mass back trajectories passing over open water and melting-sea-ice regions, also pointing to marine biological activities within the open leads in the pack ice and/or along the melting marginal sea ice zone (MIZ) being responsible for such events (Dall'Osto et al, 2017b, 2018b. Our data from Halley and the brief intercomparison with two other stations suggest that the size distributions of Antarctic sub-micrometre aerosols may have been oversimplified in the past (Ito, 1993) and that complex interactions between multiple ecosystems, coupled with different atmospheric circulation, result in very different aerosol size distributions populating the Southern Hemisphere.…”
Section: Implication For Climate and Conclusionmentioning
confidence: 99%
“…Bubble-bursting and jet drops at the ocean surface result in the production of sea spray particles composed of inorganic sea salt and organic matter (e.g., de Leeuw et al, 2011;Quinn and Bates, 2014). Among various atmospheric aerosol components, sea salt is estimated to have the largest mass emission flux and the second-largest atmospheric mass loading globally (Textor et al, 2006).…”
Section: Introductionmentioning
confidence: 99%